Pengaruh Experiential Marketing, Atmosphere Toko, Dan Sense Of Trust Terhadap Kepuasan Konsumen Mahasiswa Kedai Kopi Pete, Kota Malang - M. Aliyuddin; Rois Arifin; Eka Farida (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The aim of this research is to know satisfaction of consumers in Kopi Pete Shop in Malang City. Based on the influence of experiential marketing, shop’s atmosphere and sense of trust. This is quantitative descriptive verificative research using non probability sampling with purposive sampling method as a sampling technique. 75 respondent was picked as a sample for this research. The result shows that experiential marketing variable doesn’t affect to consumer’s satisfaction partially, otherwise the shop’s atmosphere trust affect to consumer’s satisfaction partially, sense of trust affect to consumer’s satisfaction partially. Experiential marketing, shop’s atmosphere, and sense of trust, affect simultaneously towards consumer’s satisfaction in Kopi Pete Shop Malang. Researcher hope for the next generation to add another variable, respondent’s amount and using newer theory to give interesting update in the research. Keywords : Experiential Marketing, Shop’s Atmosphere, Sense Of Trust,  Consumer’s Satisfaction